Auditor Appointment Strategy and Intragroup Value Transfers: Evidence From Family Business Groups. (July 2023) - Cheung, Yan-Leung; Haw, In-Mu; Tan, Weiqiang; Wang, Wenming
Family business groups (FBGs) typically control several member firms and can hire a single auditor or multiple auditors to audit their member firms. This article examines what type of auditor appointment strategy constrains intragroup value transfers within FBGs. Analyzing related-party transactions (RPTs) within FBGs in Hong Kong, this study provides evidence that FBGs with multiple auditors undertake more intragroup value transfers than FBGs with a single auditor. However, the adverse effect of multiple-auditor appointments is mitigated by a stronger board and higher financial reporting comparability among member firms. Using an alternative measure of intragroup value transfers, we also find that the market perceives multiple-auditor appointments as impairing audit effectiveness. Overall, our findings offer the new insight that controlling families can exploit the appointment of multiple auditors as a "divide and conquer" strategy which undermines the monitoring role of auditors against intragroup value transfers, but stronger corporate governance of member firms can mitigate the adverse effect.